Potensi Pengembangan Wisata Muslim Friendly di Pulau Bali - Dandi Darmawan; Rai Riya; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
Muslim friendly tourism has now become a global economic trend, as well as Muslim friendly tourism as an industry. The development of Muslim-friendly tourism follows the lifestyle trend of Muslims as a result of the growth in the economic capacity of people in Muslim countries, especially in Middle Eastern countries. With diverse potentials, Indonesia continues to grow to become a world leader. Several areas are advertised as Muslim-friendly destinations, and Bali is no exception. The research method used is the method of literature review and document study. Collecting primary data and secondary data. Based on information linking information from various sources, it can be concluded that Bali tourism industry players generally reject Bali as a destination with a Muslim-friendly tourism concept. The reason for the refusal is related to the sustainability of tourism in Bali, which is known as the concept of cultural tourism. Therefore, Bali is more suitable as a Muslim-friendly tourist destination, but does not include the concept of tourism.